Cardiac biomarkers and clinical scores for risk stratification in elderly patients with non‐high‐risk pulmonary embolism. (13th November 2014) - Vuilleumier, N.; Limacher, A.; Méan, M.; Choffat, J.; Lescuyer, P.; Bounameaux, H.; Aujesky, D.; Righini, M.
Abstract Objective To determine the prognostic accuracy of cardiac biomarkers alone and in combination with clinical scores in elderly patients with non‐high‐risk pulmonary embolism (PE). Design Ancillary analysis of a Swiss multicentre prospective cohort study. Subjects A total of 230 patients aged ≥65 years with non‐high‐risk PE. Main outcome measures The study end‐point was a composite of PE‐related complications, defined as PE‐related death, recurrent venous thromboembolism or major bleeding during a follow‐up of 30 days. The prognostic accuracy of the Pulmonary Embolism Severity Index (PESI), the Geneva Prognostic Score (GPS), the precursor of brain natriuretic peptide (NT‐proBNP) and high‐sensitivity cardiac troponin T (hs‐cTnT) was determined using sensitivity, specificity, predictive values, receiver operating characteristic (ROC) curve analysis, logistic regression and reclassification statistics. Results The overall complication rate during follow‐up was 8.7%. hs‐cTnT achieved the highest prognostic accuracy [area under the ROC curve: 0.75, 95% confidence interval (CI): 0.63–0.86, P < 0.001). At the predefined cut‐off values, the negative predictive values of the biomarkers were above 95%. For levels above the cut‐off, the risk of complications increased fivefold for hs‐cTnT [odds ratio (OR): 5.22, 95% CI: 1.49–18.25] and 14‐fold for NT‐proBNP (OR: 14.21, 95% CI: 1.73–116.93) after adjustment for both clinical scores and renal function. Reclassification statistics indicated that adding hs‐cTnT to the GPS or the PESI significantly improved the prognostic accuracy of both clinical scores. Conclusion In elderly patients with nonmassive PE, NT‐proBNP or hs‐cTnT could be an adequate alternative to clinical scores for identifying low‐risk individuals suitable for outpatient management.